RESEARCH ON THE CONSTRUCTION OF TEACHING ABILITY EVALUATION INDEX SYSTEM OF “DOUBLE-QUALIFIED “TEACHERS IN HIGHER VOCATIONAL COLLEGES IN CHINA - Sun Xiaoting, Peng Wenbo (Chelonian Research Foundation, 2023)
With the upgrading and optimization of economic structure, the rapid transformation of development mode, and the continuous advancement of the construction of modern economic development system, a group of high-quality technical and skilled talents are more and more needed, and vocational education, which undertakes the important task of cultivating technical and skilled talents, needs to play a vital role. However, the reality is that the contradiction between the growing demand for high-quality technical and skilled talents and the insufficient teaching ability of "double-qualified" teachers in higher vocational education is becoming increasingly prominent, which restricts the high-quality development of vocational education and then affects the quality of talent training. While the country focuses on the development of vocational education, how can the "double-qualified" teachers of higher vocational education shoulder the important task of cultivating high-quality compound and professional talents? What are the teaching abilities of "double-qualified" teachers in the teaching process? In this study, we took the "double-qualified" teachers of China's higher vocational colleges as the research object, and used the Delphi expert consultation method to study and develop the evaluation index of the teaching ability of the "double-qualified" teachers of higher vocational colleges, and constructed the evaluation model of the teaching ability of the "double-qualified" teachers of higher vocational colleges. Key words: higher vocational colleges, "double-qualified" teachers, teaching ability, evaluation index system